Marketing real people, real choices - Solomon, Michael R.; Marshall, Greg W.; Stuart, Elnora W. (Pearson Education, 2012)
Introducing marketing from a real-world, practical perspective, this text lets students see how people just like them are actually doing real marketing. Case studies focus on companies where the answers are not clear-cut.